Optimizing the Gut Microbiota for Individualized Performance Development in Elite Athletes - Nolte, Svenja; Krüger, Karsten; Lenz, Claudia; Zentgraf, Karen; Justus Liebig University Giessen (My University, 2023)
The human gut microbiota can be compared to a fingerprint due to its uniqueness, hosting trillions of living organisms. Taking a sport-centric perspective, the gut microbiota might represent a physiological system that relates to health aspects as well as individualized performance in athletes. The athletes’ physiology has adapted to their exceptional lifestyle over the years, including the diversity and taxonomy of the microbiota. The gut microbiota is influenced by several physiological parameters and requires a highly individual and complex approach to unravel the linkage between performance and the microbial community. This approach has been taken in this review, highlighting the functions that the microbial community performs in sports, naming gut-centered targets, and aiming for both a healthy and sustainable athlete and performance development. With this article, we try to consider whether initiating a microbiota analysis is practicable and could add value in elite sport, and what possibilities it holds when influenced through a variety of interventions. The aim is to support enabling a well-rounded and sustainable athlete and establish a new methodology in elite sport.
Keywords: ddc:796